COMPARISON OF PLATINUM GROUP MINERALS FROM ELUVIAL-DELUVIAL PLACER OF THE SVETLY BOR CLYNOPIROXENITE-DUNITE MASSIF (CENTRAL URALS) - R.S. Palamarchuk; S.Yu. Stepanov; D.A. Khanin; A.V. Antonov; A.A. Zolotarev (Минералогия)
Morphology and composition of platinum group minerals (PGMs) from loose sediments of eluvial-deluvial placer of the Svetly Bor clinopyroxenite-dunite massif are studied. The contours of placer mineralization and area of occurrence of primary Pt-bearing chromitites are similar. Based on the features of PGM composition, the placer belongs to Ir–Pt mineralogical-geochemical type. It is shown that placer PGMs inherits primary morphological features and the composition of placer and primary PGM assemblages are identical.